Analysis of Factor That Affect The Closure of JD.ID Ecommerce Platform - Sinaga, Devi (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2024)
There is a steady increase in platform start-ups. Despite this, many newly established companies fail within the first five years, with the majority going out of business in a shorter period of time. The cause of this kind of failure still needs to be investigated methodically. This study attempts to investigate the causes behind the failure of Â JD.ID e-commerce platform to close its market in Indonesia, despite the fact that there are many independent investigations that have offered various explanations regarding the definition of failure in jd.id general. The theoretical framework will identify the factors that affect products, finances, and markets in organizations that make start-up platforms jd.id fail. An extensive review of library research was conducted to uncover and examine the failures of the jd.id platform. His research uses websites to collect research data. The results of this study reveal that what makes the jd.id platform fail and close its market in Indonesia are product factors, market factors, and financial factors. and the jd.id business failure category falls into the inadequate earnings category.Keywords : E-Commerce, Business Failure, Factors Business Failure